The Effect of Internal Control and Organizational Governance on Fraud Prevention with Commitment as a Moderating Variable - Masdar, Rahma; Amir, Andi Mattulada; Abdullah, M. Ikbal; Pattawe, Abdul; Usman, Rudy (Institut Bisnis dan Informatika Kesatuan, 2026)
Universities managing public funds must ensure accountability and transparency, yet corruption cases show fraud remains a serious risk. This study aims to analyze the influence of internal control systems and organizational governance on fraud prevention, with organizational commitment as a moderating variable. The research method uses a quantitative approach with an explanatory design, involving employees of universities with public service agency status as respondents. Primary data were collected through questionnaires compiled based on COSO indicators, governance principles, and dimensions of organizational commitment. The analysis was conducted using Partial Least Squares (PLS)-based Structural Equation Modeling using WarpPLS 8.0. The results show that internal control systems and organizational governance have a significant positive effect on fraud prevention. Organizational commitment weakens the effect of internal control systems on fraud prevention but strengthens the effect of governance. These findings confirm that the success of control and governance systems depends not only on formal procedures but also on employee emotional attachment and loyalty to the organization. This study integrates Agency Theory and Organizational Support Theory in explaining fraud prevention mechanisms. The results provide recommendations for universities to strengthen the culture of integrity through a combination of internal control, good governance, and organizational commitment.